Urban unemployment in the EU, tertiary sector employment growth and urban size - Graham Robert Crampton (European Regional Science Association (ERSA), 1998)
The paper uses REGIO data to study recent change in unemployment in major urban areas of Europe. Previous results suggested a significant role for tertiarisation in employment, and a systematic association with urban size. This work is carried forward using more recent data on urban areas at NUTS3 level. Patterns in variation of unemployment across countries and city sizes are discussed. Econometric estimates going beyond OLS are discussed using LIMDEP software. Details on long term unemployment are only available at NUTS2 level, but this still provides useful insight for the largest EU urban areas for which the NUTS2 region is a useful approximation to the urban area. Some policy implications are also discussed, in the light of the recent debate over `Euro-sclerosis' in the labour market.
Keywords: 330